Short communication. Cloning and sequencing of partial genomic DNA fragments corresponding to the S11 and S12 alleles of the Spanish almond cultivar ‘Marcona’ - Kodad, O.; Sánchez, A.; Saibo, N.; Alonso, J. M.; Oliveira, M. M.; Socias i Company, R. (Spanish Journal of Agricultural Research, 2006)
This paper reports the cloning and partial genomic DNA sequencing of two S-RNases (S11 and S12) of almond. DNA from the Spanish almond cultivar Marcona, the most highly appreciated in Spain, was amplified by PCR using the primer pair AS1II and AmyC5R designed for the conserved regions of almond S-alleles. The cloned and sequenced S11 allele of cv. Marcona appears to be identical to that of cvs. Rumbeta and Bertina (which have been previously cloned and sequenced). This is the first time, however, that S12 has been sequenced in almond. The amplified and cloned S12 allele fragment possessed 1080 bp corresponding to the second intron and 506 bp corresponding to the second and third exons. The product of PCR-specific amplification showed that cv. Marcona and the Portuguese cultivar Pestaneta carry the same S12 allele. Knowledge of the sequences of these alleles will be helpful in the design of specific primers for S11 and S12, and could be of use when employing antisense techniques in genetic engineering projects.